"Walrasian Fixed Supply Conjecture" Versus "Contest-Nash" Solutions to Sports League Models: Game Over?. (June 2015) - Madden, Paul
Winfree and Fort (WF) recently suggested an approach to modeling basic two-team sports leagues, which requires Nash equilibrium solutions to games where investments in (not levels of) talent are the strategic variables. I comment (a) it is crucial that talent investments are the strategic variables, reworking arguments from my earlier article; (b) with nuanced but important differences from Stefan Szymanski's conclusions regarding WF, Walrasian fixed supply conjecture solutions and the invariance principle are unlikely to emerge from this approach but Contest-Nash solutions can; (d) the long-running debate alluded to in the title of this article may have run its course.